Pengaruh Kompetensi Sumber Daya Manusia Terhadap Kinerja Pengelola Koperasi Di Kabupaten Barru - Ibrahim, Lilly (Perpustakaan dan Penerbitan Unismuh Makassar, 2012)
The study aims to analyze the extent of communication competence, teamwork, leadership, termination of an analysis of the opinion that employees have on the performance of cooperatives in Barru managers.The population of this study are all managers of cooperatives in Barru with a total sample of 65 persons. Data analysis method used is multiple regression analysis using SPSS 18 in the processing of primary data, in order to obtain information about the influence of independent variables on the dependent variable either simultaneously or partially.Results showed that communication ability factor Simultaneously, the ability of cooperation, leadership, and analytical decision-making significantly influence the performance of cooperatives in Barru. Analytical decision-making variables are the dominant variables influence the performance terahadap managers of cooperatives, cooperative means that if managers can make decisions with proper analysis, the foundation managing the performance of cooperatives is also expected to increase. Partial test also showed that the analytical decision-making variables have positive and significant impact on improving the performance of cooperative managers.The author suggests that the government through the Department of Cooperatives in Barru Regency to do a series of efforts to improve the ability of managers of cooperatives through education and training activities so that the cooperative management of communication skills, collaboration skills, and analytical decision-making can be improved.